Independent dentists’ knowledge on patient safety and reporting of adverse events. Medellín, Colombia, 2017 - Calle-Henao, Natalia; Hernández-Pinillos, Paula Carolina (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Introduction: In Colombia, the Comprehensive Health Services Qualifying System (Sistema Único de Habilitación de Servicios de Salud) has been revised several times. It is currently governed by Resolution 2003 of 2014, which includes dentists as independent professionals who must abide by its content. This regulation considers healthcare quality in relation to patient safety as a key aspect for professional practice. The goal of the present study was to determine the associations between dentists’ sociodemographic characteristics, their knowledge on patient safety, and the reporting of adverse events with the patient safety perception by independent providers of the dental services in the city of Medellín. Methods: This is a descriptive, cross-sectional, analytical study in 215 independent dentists from Medellín; an empirical analytical approach was used for data collection, conducting univariate, bivariate, and multivariate statistical analysis. Results: of the population of dentists studied, 52.1% were female and 50% were 41 years or younger. The variables with statistically significant association regarding dentists’ perception on patient safety were: pursuing patient safety studies after graduation, having full qualifying standards, and have performed more than one corrective action of adverse events over the past year. Conclusions: Independent dentists generally lack knowledge on adverse events management and patient safety practices. Universities and monitoring and control bodies can promote theoretical and practical activities to improve these aspects and thus the safety of dental patients.